PENGARUH AKULTURASI BUDAYA MINANGKABAU PADA ETNIS TIONGHOA DI KOTA PADANG - Rafiq Kurniawan; Shofy Abiyah; Dendi Putra Adriyan; Wita Okta Sari; Mhd Varel Wijaya (Universitas Palangka Raya, 2023)
The aim of this research is to describe how the acculturation of Minangkabau culture influences Chinese ethnicity. Cultural acculturation can occur in all levels of society thanks to intercultural communication in society. This research was conducted in Padang City, Pondok Pondok Village, West Padang District. The research method used is a qualitative descriptive method, which describes research based on a description of the actual situation. Informants were determined using a